1993
DOI: 10.1192/pb.17.12.711
|View full text |Cite
|
Sign up to set email alerts
|

Development and audit of Charles Street Parent and Baby Day Unit, Stoke-on-Trent

Abstract: Although several studies have found the frequency of postnatal depression to range from 9 to 13%, optimal services for the recognition and management of this disorder are not fully established. There is a lacuna in the provision and costing of comprehensive services for women with postnatal mental illness, although it is recommended that each large district requires a consultant led team (three to five sessions per week) and a district or supra-district mother and baby unit (Oates 1988; Royal College of Psychi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…This specialized psychiatric day hospital in Stoke-on-Trent, Staffordshire, England, offers a comprehensive service of individual, high intensity, customized treatment to women with mental health problems associated with pregnancy and within 12 months of childbirth. The PBDU is staffed by a multidisciplinary team of psychiatrists, psychiatric nurses, an occupational therapist and a nursery nurse and offers an individually tailored package of treatments including: pharmacotherapy, individual counselling and group therapies, such as stress management and assertiveness training (Boath et al, 1995;Cox et al, 1993). Research has shown that attendance at the PBDU has greater therapeutic impact on postnatal depression than routine care and is cost-effective (Boath et al, 1999;2003).…”
mentioning
confidence: 99%
“…This specialized psychiatric day hospital in Stoke-on-Trent, Staffordshire, England, offers a comprehensive service of individual, high intensity, customized treatment to women with mental health problems associated with pregnancy and within 12 months of childbirth. The PBDU is staffed by a multidisciplinary team of psychiatrists, psychiatric nurses, an occupational therapist and a nursery nurse and offers an individually tailored package of treatments including: pharmacotherapy, individual counselling and group therapies, such as stress management and assertiveness training (Boath et al, 1995;Cox et al, 1993). Research has shown that attendance at the PBDU has greater therapeutic impact on postnatal depression than routine care and is cost-effective (Boath et al, 1999;2003).…”
mentioning
confidence: 99%